Gestión del Riesgo de Mercado como herramienta de estabilidad económica. El caso colombiano (2019)
The present paper aims to describe market risk management as a critical aspect key for avoiding financial crises and maintaining the stability of our national economic system, at the same time that the state, the financial institutions and the investors are presented as primary players in this process. The primary importance of good market risk management is highlighted to ensure adequate macroeconomic functioning of economies, especially given the advent of globalization. We continue with the government’s role as a regulator and supervisor of the risk management implemented by financial institutions. The parametric and non-parametric methodologies that a financial institution requires for calculating the VaR of a single investment and the VaR of a portfolio are then described, as well as the current regulatory situation and the proliferation of organizations involved in managing this type of risk in Colombia.